Oculocutaneous Albinism and Squamous Cell Carcinoma of the Skin of the Head and Neck in Sub-Saharan Africa. (12th August 2015) - Lekalakala, P. T.; Khammissa, R. A. G.; Kramer, B.; Ayo-Yusuf, O. A.; Lemmer, J.; Feller, L.
Abstract : Oculocutaneous albinism which is characterised by impaired melanin biosynthesis is the most common inherited pigmentary disorder of the skin and it is common among Blacks in sub-Saharan Africa. All albinos are at great risk of developing squamous cell carcinoma of sun-exposed skin, and Black albinos in sub-Saharan Africa are at about a 1000-fold higher risk of developing squamous cell carcinoma of the skin than the general population. In Black albinos, skin carcinoma tends to run an aggressive course and is likely to recur after treatment, very probably because the aetiology and predisposing factors have not changed. Prevention or reduction of occurrence of squamous cell carcinoma of the skin in Black albinos might be achieved through educating the population to increase awareness of the harmful effects of exposure to sunlight and at the same time making available effective screening programs for early detection of premalignant and malignant skin lesions in schools and communities and for early treatment.